Interpersonal and Institutional Betrayal: A Trust Game - Tortora, Leda; De Vries, Jan; Bokde, Arun (My University, 2024)
The analysis revealed that Interpersonal and Institutional Betrayal lead to varying experiences of hate. These experiences have significant implications for the aftermath endured by victims and influence the effectiveness of Restorative and Retributive mitigation strategies.
Molecules to Mind Trinity Neuroscience Research Day
Keywords: Neuroscience; Neuroscience; Reconciliation; hate; trust game; Community; Communication; Health; Relationships